Tanda-Tanda Kebesaran Allah Dalam Kehidupan Sehari-Hari: Menggali Makna Dari Alam di Sekitar Kita - Mona Putri; Shoqibah Wijaya Kusuma; Annisa Athiyah Fitri; Asep Taufik Hidayat; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article examines the signs of Allah's greatness reflected in the universe, with the aim of increasing spiritual understanding and awareness of the greatness of His creation. Through a qualitative approach, this research uses literature study, direct observation, and interviews with experts to explore various natural phenomena that demonstrate God's power and wisdom. Findings show that the wonders of astronomy, biodiversity, and the regularity of natural laws serve as clear evidence of His greatness. This research also emphasizes the importance of contemplating creation as a means of strengthening faith and gratitude. Thus, it is hoped that this article can encourage readers to admire and protect nature more as a form of devotion to the Creator.